Nur77 controls tolerance induction, terminal differentiation, and effector functions in NKT cells - Kumar, A; Hill, TM; Gordy, LE; Suryadevara, N; Wu, L; Flyak, AI; Bezbradica, JS; Van Kaer, L; Joyce, S (American Association of Immunologists, 2020)
Natural killer T (NKT) cells are self-reactive lymphocytes, yet how this lineage attains self-tolerance remains unknown. NKT cells constitutively express high levels of Nr4a1-encoded Nur77, a transcription factor that integrates signal strength downstream of the T cell receptor (TCR) within activated thymocytes and peripheral T cells. Nur77 is associated with tolerance induction in conventional T cells but is of hitherto unknown function in NKT cells. Here we report that sustained Nur77 overexpression (Nur77tg) in mouse thymocytes abrogates NKT cell development. Introgression of a rearranged Vα14-Jα18 a-chain gene into the Nur77tg (Nur77tg;Vα14tg) mouse rescued development up to an early precursor stage 0. NKT cells in bone marrow chimeras that reconstituted thymic cellularity developed beyond stage 0 precursors, yielding interleukin-4-producing NKT2 but not interferon-g-producing NKT1 cell subsets. Nonetheless, NKT cells that emerged in these chimeras expressed the exhaustion marker PD1 and responded poorly to glycolipid agonists. Hence, Nur77 integrates signals emanating from the TCR to control NKT cell tolerance, terminal differentiation, and effector functions.